2009
DOI: 10.1061/(asce)1943-4162(2009)1:1(40)
|View full text |Cite
|
Sign up to set email alerts
|

Construction Litigation, U.S. General Services Administration, 1980–2004

Abstract: This paper presents results from a study analyzing first time litigation brought against the U.S. General Services Administration for the period 1980-2004. Cases were extracted from the general services board of contract appeals and the U.S. Court of Federal Claims decisions. A total of 606 cases were considered from this time period and are characterized by their primary cause. Trend analyses were performed to determine whether the frequency of litigation has increased or decreased. Comparisons are made with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…In the construction industry, transaction hazards play a key role. First, transaction costs are important drivers of total project costs (Gebken and Gibson, ; Goetz and Gibson, ); second, disputes among project participants, including subcontractors, are common (Arditi and Chotibhongs, ; Kumaraswamy, ; Rubin and Wordes, ); and third, key success factors in construction projects include the appropriateness of the project governance mechanisms and the capability of the project managers to mitigate free‐riding and opportunism among the project constituents (Lui and Ngo, ; Odeh and Battaineh, ; Palaneeswaran et al ., ; Winch, ).…”
Section: Theory and Hypothesesmentioning
confidence: 99%
“…In the construction industry, transaction hazards play a key role. First, transaction costs are important drivers of total project costs (Gebken and Gibson, ; Goetz and Gibson, ); second, disputes among project participants, including subcontractors, are common (Arditi and Chotibhongs, ; Kumaraswamy, ; Rubin and Wordes, ); and third, key success factors in construction projects include the appropriateness of the project governance mechanisms and the capability of the project managers to mitigate free‐riding and opportunism among the project constituents (Lui and Ngo, ; Odeh and Battaineh, ; Palaneeswaran et al ., ; Winch, ).…”
Section: Theory and Hypothesesmentioning
confidence: 99%
“…Further to this, the only reference to any of the variables in the literature. Goetz and Gibson (2009) reveal that, in the period from 1980 to 2004, disputes over site conditions were 237.5 per cent less likely to lead to litigation than compared to disputes over modifications. Semple et al (1994, p. 785) identifies an “[…] increase in scope of the work, weather, restricted access and acceleration […] ” as the most common contributing factors in claims in the Canadian construction sector.…”
Section: Discussionmentioning
confidence: 97%
“…The literature covers a wide array of critical factors that result in disputes. Research from Semple et al (1994) reveal that an increase in the scope of the work acts as a primary contributing factor for dispute claims in the construction industry, while Goetz and Gibson (2009) indicate payment as a source of dispute. Further to this, an investigation by Kennedy (2006) into adjudication in the UK found that adjudication issues normally revolve around payment and valuation issues.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There have been findings that the economic circumstances surrounding a construction project can affect the number of construction claims and disputes [40,41]. Therefore, analyzing the construction disputes in the context of the construction economic situation is needed for the trend analysis.…”
Section: Construction Dispute Trends By Periodmentioning
confidence: 99%